Prices of Agricultural Land in Poland against the Background of the European Union - Firlej, Krzysztof; Kubala, Sebastian (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
Long before Poland̛s accession to the European Union, the prices of agricultural land were of interest not only to potential investors in the agri-food sector, but also to speculators, whom agroeconomists were tasked with monitoring. The aim of this study was to assess changes in agricultural land prices in Poland compared to the European Union and to identify variables that strongly depend on the average level of prices of agricultural land in the European Union. This article also demonstrates that in EU countries there is a significant correlation between agricultural land prices and the value of direct payments and the value of gross domestic product per capita.